1995
DOI: 10.1111/j.1365-3083.1995.tb03659.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Denaturation of Ovalbumin Abrogates the Induction of Oral Tolerance of Specific IgG Antibody and DTH Responses in Mice

Abstract: We have examined the effects of ingestion of chemically denatured ovalbumin (OVA) in mice. Both 8 M urea-denatured OVA (UD-OVA) and carboxymethylated UD-OVA (CM-OVA) were purified by gel filtration. Specific IgG antibody and systemic delayed-type hypersensitivity (DTH) responses to OVA were not suppressed by CM-OVA fed prior to or after immunization with OVA in complete Freund's adjuvant (CFA). When CM-OVA was used instead of OVA, for immunization, serum IgG and DTH responses to CM-OVA were orally tolerized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Using polyclonal antibodies specific for native or chemically denatured OVA, we have also shown that native OVA, but not chemically denatured OVA, is the unique molecular species in OVA-fed mouse serum [17]. Similarly, OVA was not detected in the mouse serum after ingestion of EW boiled for 60 min.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Using polyclonal antibodies specific for native or chemically denatured OVA, we have also shown that native OVA, but not chemically denatured OVA, is the unique molecular species in OVA-fed mouse serum [17]. Similarly, OVA was not detected in the mouse serum after ingestion of EW boiled for 60 min.…”
Section: Discussionmentioning
confidence: 79%
“…Absorption of minute amounts of fed proteins has been described repeatedly [17,30]. Although the effects of uptake of oral antigens are unclear, it has been postulated that the induction of oral tolerance is related to the intestinal permeation of monomeric forms of oral antigens from immuogenic aggregates [2,15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations